Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Pada Dinas Koperasi, Perindustrian Dan Perdagangan Kota Bima - M.Taufik; Mulyadin Mulyadin (Jurnal Bintang Manajemen, 2023)
This study aims to determine the effect of communication and the work environment on employee morale at the Office of Cooperatives, Industry and Trade in Bima City. The approach used in this research is using an associative approach. The sample in this research is 40 respondents. Data collection techniques used are observation, questionnaires, and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that communication (X1) and work environment (X2) have a significant effect on employee morale at the Office of Cooperatives, Industry and Trade of the City of Bima with an effect of 56.2%.